2020
DOI: 10.3390/nu12020457
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Anticancer Agents

Abstract: Flavonoids are polyphenolic compounds subdivided into 6 groups: isoflavonoids, flavanones, flavanols, flavonols, flavones and anthocyanidins found in a variety of plants. Fruits, vegetables, plant-derived beverages such as green tea, wine and cocoa-based products are the main dietary sources of flavonoids. Flavonoids have been shown to possess a wide variety of anticancer effects: they modulate reactive oxygen species (ROS)-scavenging enzyme activities, participate in arresting the cell cycle, induce apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
559
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(578 citation statements)
references
References 220 publications
8
559
0
11
Order By: Relevance
“…A variety of flavonoids, including kaempferol and quercetin, have antioxidant and pro-oxidant activities, which are involved in the anticancer effects [36]. Is CLDN2 expression affected by an intracellular-reduced condition?…”
Section: Discussionmentioning
confidence: 99%
“…A variety of flavonoids, including kaempferol and quercetin, have antioxidant and pro-oxidant activities, which are involved in the anticancer effects [36]. Is CLDN2 expression affected by an intracellular-reduced condition?…”
Section: Discussionmentioning
confidence: 99%
“…Grosso et al [ 86 ] conducted a systematic evaluation of the role of polyphenols in cancer prevention, and the analysis showed that isoflavones significantly reduced the risk of gastric, lung, breast and colorectal cancers, by directly inhibiting oxidative stress, oxidative damage, anti-angiogenesis and anti-metastasis, while total flavones had little effect on the risk of breast cancer. Another study reviewed the role of flavonoids in colon cancer risk and found that the sustained consumption of flavonoids appeared to be an effective complementary treatment that reduced colon cancer risk from cellular antioxidants and anti-inflammatory effects [ 87 ]. The study also revealed that the flavonoid subclasses had a significant synergistic effect on preventing tumorigenesis, tumor growth and promoting apoptosis of cancer cells [ 87 ].…”
Section: Bioactivities Of Polyphenolsmentioning
confidence: 99%
“…Another study reviewed the role of flavonoids in colon cancer risk and found that the sustained consumption of flavonoids appeared to be an effective complementary treatment that reduced colon cancer risk from cellular antioxidants and anti-inflammatory effects [ 87 ]. The study also revealed that the flavonoid subclasses had a significant synergistic effect on preventing tumorigenesis, tumor growth and promoting apoptosis of cancer cells [ 87 ]. Similar studies by Chang and coworkers proved that the intake of quercetin and other flavonol compounds could reduce the risk of colon cancer, while the intake of apigenin and other flavonoids could reduce the risk of rectal cancer [ 88 ].…”
Section: Bioactivities Of Polyphenolsmentioning
confidence: 99%
“…The chemopreventive character of flavonoids relies on their potential to inhibit new cancer cell development, prevent carcinogens from reaching activation sites, decrease compound toxicity by inhibiting their metabolism [ 59 ]. The molecular mechanisms responsible involve apoptosis induction, cell cycle arrest by inhibiting key regulators, metabolizing enzymes inhibition and subsequent inactivation of carcinogenic compounds, reactive oxygen species scavenging, angiogenesis inhibition, DNA repair mechanism initiation, and cancer cell proliferation and invasiveness suppression [ 56 , 59 , 60 , 61 ]. Additionally, some flavonoid compounds have shown to prevent cancer relapse and chemotherapy failure by considerably inhibiting multidrug resistance [ 59 ].…”
Section: Natural Anti-cancer Agents For Skin Cancermentioning
confidence: 99%